The Life of Jesus by Bruno Dumont - MAGNUS VON HORN (Images)
The thesis will focus on analysing what “ The Life Of Jesus” is about and how this is portrayed through the main character, Freddy. It will discuss the concept of the filmie character as a “common human being”, who does not have access to intellectual reflection and verbal articulation of emotional conflict and crisis, but who, at the same time, is capable of feeling a great deal. He feels the emotional conflict and crisis that make up the story. I will also attempt to step inside the same filmic character itself and analyse how to visualize the morals, ethics and emotions that the character cant verbalize or communicate in any direct or intellectual way. Bruno Dumont speaks about filming the inside of a person as his highest dream. I will discuss film directing using The Life Of Jesus as an example, but I will also draw on my own experiences as a filmmaker.